ANALYSIS OF THE EFFECT OF CUSTOMER BUYING INTENTION ON THE SELECTION OF THE NEW NORMAL KIT IN THE COVID-19 PANDEMIC - Golan Hasan; Richart (International Journal of Research -GRANTHAALAYAH, 2022)
This study aims to analyze the effect of Health benefit, Brand Quality, Brand Trust, and Price by mediating Perceived Value on Buying Intention. according to the requirements in the known population of 1.1 million people have visited, then based on Krejcie and Morgan table, the number of samples that must be required is 384 respondents. The data used in this study were 384 respondents. Results obtained from the Partial Least Square (PLS) approach for data analysis it is said that the Health Benefit variable has a significant effect on Perceived value, as well as Brand Quality, Brand Trust, Price variables which also have a significant effect on Perceived value. and then also has a significant effect on the perceived value variable on buying intention, as well as the health benefit variable with price which also has a significant effect on buying intention.